2001
DOI: 10.1039/b106311c
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Zn, Pb and Cd in river sediments from a lead and zinc mining area using the BCR three-step sequential extraction procedure

Abstract: The extent of pollution was investigated in sediments collected along the course of the river Meza and its tributaries in the lead and zinc mining area of the Mezica valley (Slovenia). In order to evaluate the heavy metal burden, total concentrations of Zn, Pb and Cd were determined and the partitioning of these metals between the easily and sparingly soluble sediment fractions was performed by the use of the slightly modified BCR sequential extraction procedure. The quality of analytical data was checked with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 18 publications
2
56
0
5
Order By: Relevance
“…The observed higher attachment of Cu and Zn to the RES phase is consistent with observations of Li et al (2001). The highest affinity of Zn towards RES phase was also reported by Svete et al (2001) in a study on the chemical partitioning of Zn from a mine area.…”
Section: Fractionation Of Heavy Metals In Soil Profilesupporting
confidence: 80%
“…The observed higher attachment of Cu and Zn to the RES phase is consistent with observations of Li et al (2001). The highest affinity of Zn towards RES phase was also reported by Svete et al (2001) in a study on the chemical partitioning of Zn from a mine area.…”
Section: Fractionation Of Heavy Metals In Soil Profilesupporting
confidence: 80%
“…2 and 3). This phenomenon for Pb was similar to another result (Svete et al, 2001), where authors reported that oxidisable fraction is a significant scavenger of Pb. Lead emissions are mainly from traffic and residential heating (Al-Masri et al, 2006) and around 66% of Pb being found to be associated with organic materials and this is due to incomplete burning of vehicles fuel (AlMasri et al, 2006) and a similar trend has also been observed in Nomi River sediment.…”
Section: Oxidisable Fraction (Sulphide and Organics)supporting
confidence: 76%
“…The most mobile forms of heavy metals occur in fractions I and II, that is in the exchangeable fraction and the fraction that binds with carbonates. Some authors have investigated the metal content within these fractions providing an opportunity to determine the level of mobility in bottom sediments [42,43]. These investigations provide information with respect to environmental risk.…”
Section: Resultsmentioning
confidence: 99%